Meaning Of Life In Anand Tucker's Leap Year (2010) Movie:An Existentialist Approach - Wulandari, Tika (2012)
This study is aimed to show the search of meaning of life in Leap Year movie (2010). The objective of this study is to apply the Existentialist approach to analyze the meaning of life in Leap Year. The writer uses Sartre's major point of Existentialism to answer the problem of the study. The researcher uses descriptive qualitative research. The data of the study is image and text taken from two data sources. The primary source is Leap Year movie directed by Anand Tucker, released in 2010. While the secondary data source are from other materials taken from book, internet, and journal which related to the study. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, casting, mise-en-scene, cinematography, sound, and editing are related to each other and form the unity. Second, based on the existentialist analysis, human has a freedom to choose her own way to reach the best and then responsible for her existence. Anand Tucker wants to convey a moral message that human will find the meaning of life by a tradition. The tradition is a woman can propose her boyfriend in leap year. Anna believes in this tradition because her love is unlimited. Human can show her existence to get a true love from deepest heart without thinking selfish and reaches the best for her life.